Evaluation of the Synergistic Antibacterial Effects of Fosfomycin in Combination with Selected Antibiotics against Carbapenem-Resistant Acinetobacter baumannii - Ozioma F. Nwabor; Pawarisa Terbtothakun; Supayang P. Voravuthikunchai; Sarunyou Chusri (MDPI AG, 2021)
The spread of multi-drug resistant (MDR) pathogens and the lagging pace in the development of novel chemotherapeutic agents warrant the use of combination therapy as a reliable, cost-effective interim option. In this study, the synergistic effects of fosfomycin in combination with other antibiotics were assessed. Of the 193 isolates, 90.6% were non-susceptible to fosfomycin, with minimum inhibitory concentrations (MICs) of ≥128 µg/mL. Antibacterial evaluation of fosfomycin-resistant isolates indicated multi-drug resistance to various antibiotic classes. Combinations of fosfomycin with 12 commonly used antibiotics synergistically inhibited most fosfomycin-resistant isolates. The fractional inhibitory concentration index indicated that combining fosfomycin with either aminoglycosides, glycylcyclines, fluoroquinolones, or colistin resulted in 2- to 16-fold reduction in the MIC of fosfomycin. Time-kill kinetics further confirmed the synergistic bactericidal effects of fosfomycin in combination with either amikacin, gentamicin, tobramycin, minocycline, tigecycline, or colistin, with more than 99.9% reduction in bacterial cells. Fosfomycin-based combination therapy might serve as an alternative option for the treatment of MDR A. baumannii. Further steps including in vivo efficacy and toxicity in experimental models of infection are required prior to clinical applications.